Comparative Assessment of Pulsed and Continuous LED UV-A Lighting for Disinfection of Contaminated Surfaces - Erik Kvam; Brian Davis; Kevin Benner (Life, 2022)
The germicidal efficacy of LED UV-A lighting has scarcely been compared in continuous and pulsed modes for contaminated surfaces. Herein, we compare the disinfection properties of pulsed versus continuous lighting at equal irradiances using a 365 nm LED device that replicates the doses of occupied-space continuous disinfection UV-A products. Representative organisms evaluated in this study included human-infectious enveloped and non-enveloped viruses (lentivirus and adeno-associated virus, respectively), a bacterial endospore (Bacillus atrophaeus), and a resilient gram-positive bacterium (Enterococcus faecalis). Nominal UV-A irradiances were tested at or below the UL standard limit for continuous human exposure (maximum irradiance of 10 W/m2). We observed photoinactivation properties that varied by organism type, with bacteria and enveloped virus being more susceptible to UV-A than non-enveloped virus and spores. Overall, we conclude that continuous-mode UV-A lighting is better suited for occupied-space disinfection than pulsing UV-A at equivalent low irradiances, and we draw comparisons to other studies in the literature.